Chemical Composition, Antifungal, and Cytotoxicity Activities of Inga laurina (Sw.) Willd Leaves - Carla de Moura Martins; Sérgio A. L. de Morais; Mário M. Martins; Luís C. S. Cunha; Cláudio V. da Silva; Carlos H. G. Martins; Luís F. Leandro; Alberto de Oliveira; Francisco J. T. de Aquino; Evandro A. do Nascimento; Roberto Chang (The Scientific World Journal)
The species Inga laurina is native to the Brazilian Cerrado. There are no studies about the chemical composition and biological activities of extracts of this endangered species. The ethanolic extract and its successive fractions are rich in phenolic compounds and presented good antifungal activities. HPLC/MS-MS/MS and H1/C13 analysis led to the identification of seventeen compounds, most of which are gallic acid derivatives, myricetin and quercetin glycosides. The ethyl acetate fraction (EAF) contained high levels of total phenolics, expressed in milligrams of gallic acid equivalents per gram of extract (475.3 ± 1.9 mg GAE gextract-1) and flavonoids expressed in milligrams of quercetin equivalents per gram of extract (359.3 ± 10.6 mg QE gextract-1). This fraction was active against fungi of the Candida genus. The EAF showed MIC value 11.7 μg mL−1 against C. glabrata and a selectivity index of 1.6 against Vero cells. The flavonol glycoside myricetin-3-O-rhamnoside was isolated for the first time from the Inga laurina. These results make I. laurina a promising plant as a source of pharmaceutical and biological active antifungal compounds.